DEMOGRAPHIC TRANSITION AND SUSTAINABLE COMMUNITIES IN MALAYSIA - Elsawahli, Hanan; Ahmad, Faizah; Ali, Azlan Shah (PLANNING MALAYSIA, 2016)
As a developing country, Malaysia is undergoing a demographic transition from a high fertility and mortality rural society towards an industrialised society with low fertility and mortality rates. This transition involved an increased growth rate of elderly population. The number of elderly has risen from 1.4 million in 2000 to 2.1 million in 2010 and is projected to be 3.4 million by 2020. A population aging needs to accumulate assets in order to achieve sustainable development goals. This represents the main challenge to planners and policy makers in terms of designing aged-friendly neighbourhoods to meet the elderly needs. This paper aims to review the population aging trends and policy framework available for the elderly in Malaysia. The paper further discusses the sustainable neighbourhoods related to active aging. The paper concludes by identifying fundamental gaps in both knowledge and policy associated with planning for the aging population and successful aging.